Review of the Entertaining Virology book by Professor F. I. Ershov, Academician of the Russian Academy of Sciences, Moscow, 2023, «Geotar Media», 157 p. Popular Science Publication - A. V. Pronin; G. A. Galegov; V. L. Andronova (Антибиотики и Химиотерапия)
.